Pre-competitive anxiety and self-confidence in pan american gymnasts - Ceballos Gurrola, Oswaldo; Pineda Espejel, Heriberto Antonio; López Walle, Jeanette M.; Tristán Rodríguez, José Leandro; Medina Villanueva, Mireya (2013)
This study aimed to examine the intensity and direction of pre-competitive anxiety indicators (both somatic and cognitive), as well as self-confidence, in gymnasts participating in the 2011 Pan American Games. Sixty male and female artistic gymnasts participated, with ages ranging from 15 to 30 years (M = 21.04 years, SD = 4.016). The Revised Competitive State Anxiety Inventory-2 (CSAI-2R, Andrade, Lois, & Arce, 2007; Cox, Martens, & Rusell, 2003) and the direction scale by Jones and Swain (1992) were both administered. The results revealed that the intensity and direction of cognitive anxiety were positively correlated with the intensity and direction of somatic anxiety (r = .55 and r = .53, respectively), while self-confidence was negatively correlated with the intensity of cognitive anxiety (r = - 305) and also predicted it (β = - .192). Women reported significantly higher perceived somatic anxiety levels (2.79) than men (2.48). In conclusion, high levels of self-confidence decreased the perception of cognitive anxiety as being debilitative to gymnasts competing at the Pan American level.